Suppressive effects of the antiandrogen agent, chlormadinone acetate and the 5α-reductase inhibitor, dutasteride on prostate weight and intraprostatic androgen levels in rats - Kobayashi, Hideo; Gotanda, Kotaro; Shibata, Yasuhiro; Watanabe, Jun-ichi; Nakano, Youichi; Shinbo, Atsushi; Suzuki, Kazuhiro (Arzneimittelforschung, 2011)
The objectives of this study were to investigate whether Chlormadinone acetate (CMA, Prostal®, CAS 302-22-7) more markedly decreased ventral prostate and seminal vesicle weights and exerted more beneficial effects on intraprostatic androgen levels than dutasteride (DUT, CAS 164656-23-9) in rats. Dose-dependent inhibiting effects on prostate and seminal vesicle enlargement were observed after the 14-day administration of CMA (30, 100 mg/kg/day) and DUT (0.3, 1 mg/kg/day). The prostate atrophy rates calculated as the percentages relative to the vehicle-treated group were 50.5 and 67.9% with 30 and 100 mg/kg CMA and 34.9 and 37.0% with 0.3 and 1 mg/kg DUT, respectively, and the atrophying effect of CMA was significantly greater than that of DUT (ρ < 0.05). The results of 7-day administration were similar to those of 14-day administration. While CMA dose-dependently and significantly (p < 0.05) reduced the testosterone (T) and di-hydrotestosterone (DHT) concentrations in prostate, DUT reduced the DHT concentration but markedly increased the Τ concentration (20-40 times). Even though it was carried out in rats, this study revealed for the first time that the antiandrogen CMA showed a stronger atrophying effect than the 5α-reductase inhibitor DUT on direct comparison. The difference between the atrophying effects of CMA and DUT is considered to be attributed to the present results that CMA reduced the concentrations of both androgens (T and DHT) in prostate but DUT did not, and the fact that CMA has a potent androgen receptor-blocking action but DUT does not.
Keywords: Benign prostatic hyperplasia; Chlormadinone acetate; Dihydrotestosterone; Dutasteride; Rat prostate; Testosterone